TERAPI BERMAIN CLAY TERHADAP KECEMASAN PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) YANG MENJALANI HOSPITALISASI DI RSUD BANJARBARU - Dayani, Nor Ella; Budiarti, Lia Yulia; Lestari, Dhian Ririn (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Hospitalization is a condition that causes a person should stay in the hospital for treatment andmedication. One of the possible nursing interventions for the children to reduce their anxiety duringhospitalization is through play therapy such as clay play. The purpose of this study was to find out theeffectiveness of clay therapy on the anxiety in preschool children (3-6 years) during hospitalization inBanjarbaru Public Hospital. This study was quasi experimental with a pretest-posttest non equivalentcontrol group design. The accidental sampling technique was used in this study to select the samplesof 26 preschool children. The samples were divided into two groups, an experimental group and acontrol group, each of which consisted of 13 children. Child’s anxiety was measured using thePreschool Anxiety Scale Revised (2010). The data were collected through measuring pre and postanxiety on both groups. The statistical results using t-independent test showed that p-value was0.000<α 0.05, indicating that there were the effectiveness of clay therapy on reducing anxiety inpreschool children (3-6 years) during hospitalization in Banjarbaru Public Hospital.